Pengembangan Game Edukasi Sebagai Alat Evaluasi untuk Mendukung Pembelajaran IPA Berbasos Education for Sustainable Development (ESD) - Dita Nurul Asyifa; Suroso Mukti Leksono; Septi Kurniasih (PendIPA Journal of Science Education, 2026)
Education for Sustainable Development (ESD) plays a crucial role in supporting the implementation of Sustainable Development Goals (SDGs) within learning environments. However, preliminary research indicates that the integration of ESD ini junior high school science curricula remains suboptimal. Given this context, this study aims to evaluate the validity of, and student responses to, educational games used as assessment tools in ESD-based science learning. The study employs a Research and Development (R&D) methodology utilizing the ADDIE model, limited to the development stage. Expert validation yielded a score of 89.92% (highly valid), while student responses demonstrated an 84.57% positive feedback rate (highly positive). These findings indicate that educational games serve as a valid and effective evaluation tool in science learning.